2015
DOI: 10.4103/0250-474x.169035
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical Screening, proximate analysis and antioxidant activity of Dracaena reflexa lam. leaves

Abstract: In the present study, the antioxidant activity of successive leaf extracts of Dracaena reflexa was investigated using the scavenging activity on 1,1-diphenyl-2-picrylhydrazyl and reducing power by ferric reducing antioxidant power assay. Methanol extract was found potent in both the assays. IC50 values of 1,1-diphenyl-2-picrylhydrazyl assay for methanol extract was 0.97 mg/ml and ferric reducing antioxidant power value for the same is 1.19. Phytochemical screening, proximate analysis and total phenolic content… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
3
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 15 publications
2
22
3
1
Order By: Relevance
“…The proximate analysis of the plant extract was carried out to evaluate its moisture, total ash, protein and fat content. It is a very important technique for the product development and quality control or regulatory purposes in the food industry and also for the purity and quality test of crude drugs in pharmaceutical industry [30]. Our study results demonstrated that the methanolic plant extract had a low moisture content which indicates that the preservation period of the extract will be high as it is evident that moisture content in the range of 5-15% are good for formulating and also hinder the microbial growth [31].…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…The proximate analysis of the plant extract was carried out to evaluate its moisture, total ash, protein and fat content. It is a very important technique for the product development and quality control or regulatory purposes in the food industry and also for the purity and quality test of crude drugs in pharmaceutical industry [30]. Our study results demonstrated that the methanolic plant extract had a low moisture content which indicates that the preservation period of the extract will be high as it is evident that moisture content in the range of 5-15% are good for formulating and also hinder the microbial growth [31].…”
Section: Discussionmentioning
confidence: 68%
“…The secondary metabolites (phytochemicals) of a plant extract are responsible for the pharmacological actions of that plant or plant parts and thus estimation of those bioactive compounds may be used to treat chronic as well as infectious diseases [30]. Our study was an evidential approach to ascertain the mentioned pharmacological functions of L. sativus L. seeds and found to have the presence of alkaloids, carbohydrates, reducing sugar, flavonoids, terpenes, phenols, proteins and amino acids, and tannins in the plant extract.…”
Section: Discussionmentioning
confidence: 99%
“…Total phenolic content could be regarded as an important indication of antioxidant properties of plant extracts 18 . Tannins are major source of phenolic compounds and are good radical scavengers and antibacterial agents 19 . It has been confirmed that consumption of phenolic rich foods or beverages prevent diseases, such as cancer, heart disease, inflammation, arthritis, immune related diseases, neurodegenerative diseases and diabetes.…”
Section: Resultsmentioning
confidence: 99%
“…In this study, the addition of Dracaena angustifolia leaves aqueous extract to milk toffee was responsible to the accumulation of reducing sugars. Dracaena angustifolia leaves are source of sugar as its powder consists of 86.01% carbohydrates and part of it is sucrose (Shukla et al, 2015). Sucrose is abundant in plants (Suwarno et al, 2015).…”
Section: Reducing Sugar Contentmentioning
confidence: 99%